2019
DOI: 10.1080/20008198.2019.1654063
|View full text |Cite
|
Sign up to set email alerts
|

Domestic violence victims in a hospital setting: prevalence, health impact and patients’ preferences – results from a cross-sectional study

Abstract: Lampe (2019) Domestic violence victims in a hospital setting: prevalence, health impact and patients' preferences-results from a cross-sectional study,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 40 publications
2
24
0
2
Order By: Relevance
“…Examining the prevalence of TBI among a group of domestic violence victims, researchers found that 88% of the women studied experienced more than one injury, and 81% of them had experienced loss of consciousness due to their injuries [54]. Mounting research indicates that mental health challenges domestic violence victims face may be even more disheartening [57][58][59]. Results from a meta-analysis of 207 studies show that depression, anxiety, posttraumatic stress disorder, antisocial personality disorder, and borderline personality disorder are common among domestic violence victims [57].…”
Section: Study Protocol Registration: Prospero Crd42020194003mentioning
confidence: 99%
“…Examining the prevalence of TBI among a group of domestic violence victims, researchers found that 88% of the women studied experienced more than one injury, and 81% of them had experienced loss of consciousness due to their injuries [54]. Mounting research indicates that mental health challenges domestic violence victims face may be even more disheartening [57][58][59]. Results from a meta-analysis of 207 studies show that depression, anxiety, posttraumatic stress disorder, antisocial personality disorder, and borderline personality disorder are common among domestic violence victims [57].…”
Section: Study Protocol Registration: Prospero Crd42020194003mentioning
confidence: 99%
“…An American study reported that only 12% of adults presenting at an emergency department were screened for intimate partner violence, and out of those that were screened, the healthcare providers reported difficulty asking questions regarding intimate partner violence (Krimm and Heinzer 2002). A study conducted at the University Hospital of Innsbruck in Austria reported that only 4.8% inpatients and outpatients from seven departments (otolaryngology, trauma surgery, neurosurgery, neurology, gynecology, internal medicine, radiology) were asked about intimate partner violence (Riedl et al 2019).…”
Section: Lack Of Comprehensive Intimate Partner Violence Training Leamentioning
confidence: 99%
“…However, patients find it more difficult to disclose intimate partner violence when not directly asked by their healthcare provider (Trevillion et al 2013). The fear that asking women about intimate partner violence within the healthcare setting can lead to re-traumatization can be mitigated by findings that most patients, both with a history (78.2%) and without a history of violence (72.9%), were open to being asked about domestic violence (Riedl et al 2019). In fact, a majority of women who had a lifetime history of intimate partner violence and were screened felt "extremely" or "very satisfied," and 53% were "extremely" or "very comfortable" comfortable with intimate partner violencerelated discussions (Swailes et al 2017).…”
Section: Importance Of Training Healthcare Providers About Intimate Pmentioning
confidence: 99%
“…(16,17) Of the most associated domestic post-aggression psychic consequences, depression and post-traumatic stress syndrome are representative. (18) From the psychological point of view, the most common consequences are the loss of selfesteem, anxiety and vulnerability. The psychologically and psychiatric well-being is on the same place as the somatic well-being and for which, also, a material quantification cannot be established.…”
Section: Psycho-social Contextmentioning
confidence: 99%